2022
DOI: 10.1136/bmjopen-2022-068575
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe disease and impact of severity on pregnant women with COVID-19: a case–control study based on data from a nationwide survey of maternity services in Japan

Abstract: ObjectiveTo identify independent risk factors for severe COVID-19 in pregnant women and to evaluate the impact of disease severity on preterm birth.DesignA case–control study based on data from a nationwide questionnaire-based survey of maternity services in Japan.SettingA questionnaire was mailed to all 2135 delivery institutions in Japan between July and August 2021. A total of 1288 institutions responded (60% of all delivery institutions in Japan). 566 facilities reported having cared for pregnant women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…The majority of pregnant women with COVID-19 were either asymptomatic or experienced mild symptoms (97.4%), while only eight cases (2.6%) were classified as moderate to severe. Consistently, multiple studies during the same period reported that mild cases accounted for 79.8% to 94.6% among pregnant women with SARS-CoV-2 infection ( Arakaki et al, 2022 ; Kumari, Anand & Vidyarthi, 2022 ; Samadi et al, 2021 ). The most common symptoms observed in SARS-CoV-2-infected pregnant women were influenza-like symptoms (including fever, cough, and sore throat), myalgia, and fatigue, which is consistent with observations made by Samadi et al (2021) .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The majority of pregnant women with COVID-19 were either asymptomatic or experienced mild symptoms (97.4%), while only eight cases (2.6%) were classified as moderate to severe. Consistently, multiple studies during the same period reported that mild cases accounted for 79.8% to 94.6% among pregnant women with SARS-CoV-2 infection ( Arakaki et al, 2022 ; Kumari, Anand & Vidyarthi, 2022 ; Samadi et al, 2021 ). The most common symptoms observed in SARS-CoV-2-infected pregnant women were influenza-like symptoms (including fever, cough, and sore throat), myalgia, and fatigue, which is consistent with observations made by Samadi et al (2021) .…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, maternal infection may increase the likelihood of adverse outcomes in neonates through vertical transmission ( Adhikari et al, 2022 ; Kotlyar et al, 2021 ). Recent investigations have reported that a significant proportion of infected pregnant women, ranging from approximately 79.8% to 94.6%, experience mild to moderate symptoms of COVID-19, while approximately 1.99% to 16.7% develop severe disease ( Arakaki et al, 2022 ; Kumari, Anand & Vidyarthi, 2022 ; Samadi et al, 2021 ). Additionally, several studies have shown an increased hospitalization rate and a higher incidence of preterm births associated with COVID-19 in pregnant women compared to non-pregnant individuals ( Ellington et al, 2020 ; Sutton et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For COVID-19-infected pregnancy, a report from 60% of all delivery institutions in Japan showed that severe COVID-19 in pregnant women was associated with increased preterm births 19 . Additionally, cumulative evidence indicates that COVID-19 increases the risk of pregnancy complications such as pre-eclampsia, preterm birth, stillbirth, and low birth weight 20 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of pregnant women infected during the pandemic is small. In Japan, 1043 pregnant women had COVID-19 infection between July 2020 and June, 2021, and 5.4% of them www.nature.com/scientificreports/ had severe disease 19 . Therefore, COVID-19 alone may not be sufficient to explain the increased adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%